Sistem Klasifikasi Sampah Otomatis Berbasis Deteksi Objek Real-Time Pada Single Board Computer Dengan Algoritma YOLO - Firdaus, Ahmad Zaki; Lelono, Danang; Natan, Oskar (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2025)
The development of an automatic waste classification system based on real-time object detection using the YOLO (You Only Look Once) algorithm on a Raspberry Pi 5 Single Board Computer (SBC) is the main focus of this final project. The main issue addressed is the increasing accumulation of waste, particularly in Indonesia, which requires an effective solution for automatic waste sorting. The system is designed to detect and sort plastic and metal waste in real-time using deep learning and computer vision technologies.This research employs the YOLO11n model, trained on a dataset of plastic and metal waste. The training process involves data augmentation techniques such as rotation and grayscale to enhance dataset variability. The training results show a mean Average Precision (mAP) of 98.44% on testing data. The system is implemented on a Raspberry Pi 5, with the model converted to NCNN format to improve inference speed. Testing results indicate that the system can achieve a speed of 8.90 FPS with a latency of 110 ms, meeting the criteria for a real-time system.